PENGARUH JARAK TANAM DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Risqan Fitrah Manik; Nurhayati Nurhayati; Erida Nurahmi (Universitas Teuku Umar, 2019)
Effect of Plant Spacing and Dosage Manure on Growth and Yield of Shallots (Allium ascalonicum L.). This study aims to determine the effect of plant spacing and doses of manure is right for the growth and yield of onion maximum. This research was conducted at the Agricultural Research Station, substations Organic Horticulture Darussalam, Banda Aceh. This research has been conducted on the month in March 2016 to May 2016. This study used a randomized block design (RAK) factorial 2 x 4 with three replications, so that there are 8 combined treatments and 24 experimental units. Factors studied were plant spacing which consists of two levels ie (20 cm x 15 cm) and (20 cm x 25 cm) and the dose of manure which consists of four levels ie (without manure), (10 ton ha-1) , (20 ton ha-1) and (30 ton ha-1). The results showed that the spacing of significant effect on the wet weight berangkasan per plot and the dry weight of tuber per plot, plant height significantly affected the age of 30 HST and berangkasan dry weight per plot. Influential no significant effect on plant height at 15 and 45 days after planting, leaf number aged 15, 30 and 45 days after planting, the number of tillers per hill, tuber number per hill, wet weight berangkasan per clump, dry weight berangkasan per clump, dry weight of tuber per hill. Growth and the best results encountered at a spacing of 15 cm x 20 cm. Dose manure no real effect on all the observed variables. There was no significant interaction between treatment and dose spacing of manure, so there is no relationship between the two factors. Keywords : onion, plant spacing and doses of manure